Assessment of the impact of productive forces, infrastructure and social sphere facilities location features on the efficiency of economic activities of enterprises in Ural Federal District municipalities - I.V. Naumov; N.L. Nikulina (Векторы благополучия: экономика и социум)
The assessment of productive forces, availability of infrastructure and social facilities location is especially relevant for improvement of strategies of socio‐economic development of territories at municipal and regional levels. The article presents the author's methodological tools, which are based on the use of multivariate analysis not only for comparison of municipalities by availability of resources and infrastructure for development, but also for comparison of results of enterprises activity in their territory with provision with these resources. The authors have carried out a theoretical review of works devoted to application of multivariate analysis for assessment of socio‐economic processes. The developed methodological approach to multivariate analysis of productive forces, infrastructure and social facilities location in territorial systems made it possible to analyze the results of activity of enterprises operating in municipalities of the Ural Federal District and their grouping; to assess availability of transport, energy and engineering infrastructure, social facilities and location of productive forces in municipalities of the Urals Federal District by selected groups and their effect on results of enterprises activity using spatial regression modeling, as well as to identify directions of development of infrastructure and social sphere in municipalities. Multidimensional analysis of the distribution of productive forces (enterprises, labor and investment resources), transport, energy and engineering infrastructure, social facilities showed spatial heterogeneity and fragmentation of their distribution. The conducted regression analysis confirmed the influence of individual elements of infrastructure and the social sphere on the intensity of the results of enterprises activities and the importance of attracting labor resources to improve it in all groups of municipalities.